The complex socio-ecological landscape in Latin America: Transdisciplinary knowledge production to address diversity - Steven Mons; Nohra León Rodríguez (European Review of Latin American and Caribbean Studies, 2023)
We start this article by seeking analogies between the cultural landscape and socio-ecological system concepts. Whereas the former has played a pivotal role in geographical research since its introduction in the nineteenth century, the latter has only recently become popular in inter- and transdisciplinary science. The results of this theoretical and conceptual endeavour are used to build a distinctive analytical category: the ‘complex socio-ecological landscape’. We then apply this novel concept to the Coffee Cultural Landscape of Colombia, declared a UNESCO World Heritage Site in 2011. In doing so, we demonstrate that this landscape in fact exhibits complex adaptive behaviour. We end the article with an analysis of the Cañamomo-Lomaprieta indigenous reservation in the north of the Coffee Cultural Landscape. Participatory mechanisms of transdisciplinary knowledge production have stimulated the emergence of an ancestral governance system in Cañamomo-Lomaprieta, which has reduced the vulnerability of its socio-ecological systems to the effects of small-scale gold mining activities. This case provides important insights into how to stimulate transdisciplinarity in other complex socio-ecological landscapes in Latin America that bear the brunt of extractive activities. Resumen: ‘Paisaje socioecológico complejo’ en Latinoamérica: Conocimiento transdisciplinario para tratar la diversidad Comenzamos este artículo buscando analogías entre los conceptos de paisaje cultural y sistema socioecológico. Mientras que el primero ha desempeñado un papel fundamental en la investigación geográfica desde su introducción en el siglo XIX, el segundo se ha hecho popular solo recientemente en la ciencia inter y transdisciplinaria. Los resultados de este esfuerzo teórico y conceptual se utilizan para construir una categoría analítica distintiva: el ‘paisaje socioecológico complejo’. Luego aplicamos este novedoso concepto al Paisaje Cultural Cafetero de Colombia, declarado Patrimonio de la Humanidad por la UNESCO en 2011. Mostramos que este paisaje efectivamente exhibe un comportamiento adaptativo complejo. Finalizamos el artículo con un análisis del resguardo indígena Cañamomo-Lomaprieta en el norte de este paisaje. Mecanismos participativos de producción de conocimiento transdisciplinario han estimulado el surgimiento de un sistema de gobernanza ancestral en Cañamomo-Lomaprieta, lo que ha reducido la vulnerabilidad de sus sistemas socioecológicos ante los efectos de las actividades de minería aurífera a pequeña escala. Este caso permite comprender cómo se puede estimular la transdisciplinariedad en otros paisajes socioecológicos complejos en América Latina afectados por actividades extractivas.